Solvent-free hydroxylation of unactivated C-H bonds in small molecules and macromolecules by a Fe complex - Chatterjee, Debasmita; Sajeevan, Amritha; Jana, Sandipan; Birajdar, Rajkumar S.; Chikkali, Samir H.; Sivaram, Swaminathan; Sen Gupta, Sayam (ACS CATALYSIS, 2024)
Keywords: Ball milling; solid-state C-H hydroxylation

Synthesis of imine-phenoxy ligated palladium complexes for norbornene homopolymerization - Birajdar, Rajkumar S.; Gupta, Poonam; Gonnade, Rajesh G.; Chikkali, Samir H. (Inorganic Chemistry, 2024)
Metal complexes with tunable ligands play a crucial role in olefin polymerization and impart control over molecular weight, crystallinity, and stereoregularity. We report the single-step synthesis of imine-phenoxy ligands in excellent yields (81-93%). The identity of electronically tuned imine-phenoxy ligands was unambiguously ascertained by using a combination of spectroscopic and analytical methods. These ligands were treated with [Pd(COD)MeCl] in the presence of 2,6-lutidine, resulting in the formation of discrete mononuclear palladium complexes Pd1-Pd4 in excellent yields. 1-2D NMR spectroscopy, mass spectrometry analysis, and single-crystal X-ray diffraction confirmed the identity of the palladium complexes. X-ray analysis revealed a distorted square planar geometry around the palladium center. Proton NMR analysis suggested that the Pd1 catalyst was deshielded, indicating electronically deficient palladium metal compared to the other complexes. Moreover, the Pd1 catalyst showed the highest buried volume percentage (%Vbur = 44.9). When exposed to norbornene, Pd1-Pd4 were found to be active and produced poly(norbornene) (PNB). High-temperature SEC analysis revealed that the electronically deficient and sterically hindered Pd1 catalyst produced the highest molecular weight polymer (PNB 37.4 kDa). Boron and aluminum-based cocatalysts were screened, and MMAO was found to outperform others with high catalytic activity (up to 63.2 x 105 g of PNB (mol Pd)-1 h-1).